ANALYZING FACTORS THAT INFLUENCE CREDIT DECISION MAKING AT BRI BRANCH OFFICE TAHUNA - Claudyanti Jeivi Lahopang; Maryam Mangantar; Maria V. J. Tielung (Jurnal EMBA : Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2023)
PT. Bank Rakyat Indonesia (Persero) Tbk Branch Office Tahuna focuses on services to small communities in helping capital problems in an effort to improve living standards for the better. The credit facilities provided are Kredit Usaha Rakyat (KUR) and Kredit Umum Pedesaan (KUPEDES). KUR and KUPEDES can be used to meet business capital needs so as to facilitate and improve operational products, and also to maintain the continuity of the business activities of prospective customers. Credit decision making is a process that is carried out by the customer when taking credit, then the customer chooses one alternative from several available alternatives. Credit decision making at Bank Rakyat Indonesia (BRI) Branch Office Tahuna can show the level of customer confidence in the bank's credit products. Thus the customer's decision to take credit becomes very important for a bank in improving the existence of the bank in order to survive in the midst of increasingly fierce competition. The objectives of this study are to reveal the influence of interest rates, credit procedures, and service quality on credit decisions making at BRI Branch Office Tahuna. The analytical method used is Multiple linear regression. Based on the results of the analysis and discussion using Multiple linear regression and classical assumption test, it is concluded that the results of the hypothesis test found that simultaneously interest rates, credit procedures, and service quality on credit decisions making at BRI Branch Office Tahuna, but the results of the hypothesis test found that partially interest rates has no significant effect on credit decisions making.. For BRI Branch Office Tahuna to maintain and improve the Interest Rate, Credit Procedure, and Service Quality again so that it will make its consumers more loyal to the brand also satisfied. Keywords: interest rate, credit procedure, service quality, credit decision making.